(untitled) (Indus Journal of Bioscience Research, 2025)
Background: The WHO (2008) Surgical Safety Checklist (SSC), has been greatly promoted worldwide as an improved tool for standardizing communication, teamwork, and adherence to essential safety practices during surgical procedures to increase patient safety. The objective of this study is to identify and analyze the barriers to the effective implementation of the WHO SSC in many tertiary hospitals of Peshawar, Pakistan. Methodology: For this purpose cross sectional descriptive research study at Maqsood Medical complex Peshawar was used. For sample size, Slovin’s formula estimates a total of 42 participants, including physicians, nurses, anesthesia staff, OT technologists and OT managers. Structured questionnaires were used to collect the data from individual experiences, interprofessional dynamics and organizational factors that affect SSC implementation. Results: Various key barriers to the consistent application of the WHO SSC in the tertiary care hospitals of Peshawar were identified. 23.8% indicated high levels of resource constrains including shortages of materials, staffing and equipment as a major limitation. Furthermore, 26.2% of the participants replied that the compliance reviews were infrequently conducted, suggesting that there was not sufficient oversight and accountability. Even though 76.2% of respondents stated they received incentives for SSC adherence, the degree of inconsistency in this provided incentive structure offers space for improvement. Moreover, only 47.6% of respondents confirmed full integration of the SSC within the emergency surgery protocols and thus a gap in the use of the SSC in high stakes situation. Generally, the supporters of SSC saw hospital culture and leadership support to the initiative in a positive light, with 81% of the respondents agreeing that the administration promoted the use of SSC visibly. The strong opinion was however complemented by a minority dissenting voice (4.8 % disagreeing and 14.3 % neutral), specifically that stronger cultural reinforcement of patient safety values is required. As other barriers, there was lack of staff involvement, improper training, reluctance to change and vague communication about the benefit of the SSC. Conclusion: There is a complex interaction of resource constraint, cultural and leadership deficiencies and protocol inadequacy that prevent the implementation of the WHO Surgical Safety Checklist in Peshawar tertiary care hospitals. These barriers need dealing with in various ways, from better use of resources, blanket emergency protocols, greater leadership support and staff training, targeted. These findings emphasize the need for context specific strategies in overcoming unique low resource challenges for transformative innovations to be achieved. Awareness of these barriers can help in achieving sustainable adoption of the SSC in Peshawar and similar areas, leading to an improvement in surgical safety and patient outcomes.